Design and Performance of Hybrid PV/T Solar Water Heaters - Tripanagnostopoulos, Yiannis; Kalogirou, Soteris A.; Souliotis, Manolis; Charalambous, P. G. (My University, 2004)
The hybrid Photovoltaic/Thermal (PV/T) solar systems can simultaneously provide electricity and heat, achieving a higher conversion rate of the absorbed solar radiation than standard PV modules. When properly designed PV/T systems can extract heat from PV modules, heating water or air, aiming to reduce the operating temperature of PV modules and to keep the electrical efficiency at a sufficient level. In this paper we present design considerations for the hybrid PV/T solar systems that are investigated at the University of Patras. The systems are analyzed with respect to their design, electrical and thermal energy output for the pc-Si and a-Si PV module types under the climatic conditions of Patras. In addition, the results from TRNSYS simulation carried out on similar PV/T type systems at the Higher Technical Institute in Nicosia are presented, giving guidelines for their application. The optimum water flow rate is found to be 25 lt/hr, which is low enough to enable the system to work in thermosyphon mode and the solar contribution is 49%.
Keywords: Hybrid Photovoltaic/Thermal (PV/T); PV/T solar systems